Examining the Relationship Between AI Chatbot Use Frequency and English Speaking Skills among the 2023 Cohort of English Education Students at UIN Datokarama Palu - Linda; Nur Asmawati; Ma'rifah Nurmala; Zul Aini Rengur (Sakura Digital Nusantara, 2026)
The rapid adoption of artificial intelligence (AI) chatbots in English language learning has created new opportunities for autonomous speaking practice; however, empirical evidence regarding whether the frequency of AI chatbot use is associated with learners’ speaking skills remains limited. This study aimed to examine the relationship between AI chatbot use frequency and the English speaking skills of the 2023 cohort students in the English Language Education Program at UIN Datokarama Palu. A quantitative correlational design was employed involving 15 students selected through purposive sampling based on predetermined inclusion criteria. Data were collected using a validated questionnaire to measure AI chatbot use frequency and a speaking test assessing two indicators, namely fluency and pronunciation. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, the linearity test, and the Pearson Product Moment correlation test with the assistance of IBM SPSS. The findings indicated that the participants demonstrated relatively high AI chatbot use frequency and fairly good English speaking skills. However, the Pearson Product Moment correlation analysis revealed no statistically significant relationship between AI chatbot use frequency and English speaking skills (r = 0.010, p = 0.972). These findings suggest that frequent AI chatbot use alone does not necessarily improve students’ fluency and pronunciation. Therefore, AI chatbots should be integrated with structured pedagogical strategies and meaningful communicative activities to optimize their contribution to English speaking development in higher education.